MANAJEMEN SENI PERTUNJUKAN KRATON YOGYAKARTA SEBAGAI PENANGGULANGAN KRISIS PARIWISATA BUDAYA - Sutiyono Sutiyono (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
This study was aimed at investigating the management which was used to do the traditional performing art in Yogyakarta palace as a form of overcoming the cultural tourism crisises. The research used qualitative approach. Participant obser- vations,  indepth interviews,  documentation  study were conducted  to collect  data. The results show that  the management which was used to doing the traditional per- forming arts in Yogyakarta  palace used management  functions,  like performance programe  (planning),  performance  actuating,   performance  organize  (organizing), and performance controll (controlling). The management applications could be used by Yogyakarta palace as  a form of  overcoming the cultural tourism crisises